2016
DOI: 10.3844/ajptsp.2016.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Stage Specificity of Eurycomanone Isolated from <i>Eurycoma longifolia</i> on <i>Plasmodium falciparum</i> Cycles

Abstract: Eurycomanone is the most active compounds in the roots of Eurycoma longifolia and shown to have in vitro antiplasmodial activity. However, the stage of Plasmodium falciparum cycles which are sensitive to eurycomanone have not been investigated. This study was conducted to investigate stage specificity of eurycomanone at various stages of P. falciparum life cycles. Stage specificity of eurycomanone at various stages of P. falciparum was performed on P. falciparum culture in vitro. A total of 100 µL of solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…This indicated that Plasmodium growth inhibited by 25µg/mL of F4.7 fraction treatment. The same results were shown in other studies using 100ng/mL of eurycomanone with an incubation time of 72h which produced 90% inhibition with Plasmodium which was discovered to be dominant in the ring and throphozoites stage (Sholikhah et al, 2016). It indicates that based on microscopic assay, F4.7 has high inhibition on Plasmodium.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This indicated that Plasmodium growth inhibited by 25µg/mL of F4.7 fraction treatment. The same results were shown in other studies using 100ng/mL of eurycomanone with an incubation time of 72h which produced 90% inhibition with Plasmodium which was discovered to be dominant in the ring and throphozoites stage (Sholikhah et al, 2016). It indicates that based on microscopic assay, F4.7 has high inhibition on Plasmodium.…”
Section: Resultssupporting
confidence: 86%
“…The two methods have their own objectives, advantages, and limitations. Thin blood films are preferred to examine the morphology of parasites and to determine species (Bejon et al, 2006) and the staging of Plasmodium (Sholikhah et al, 2016). Microscopic method using thin blood smear with Giemsa stain is a standard method for observation (Hall & Fauci, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…This research demonstrated that F6 of T. diversifolia revealed cytocidal effects at early rings to late trophozoites which is similar with eurycomanone, an isolate of Eurycoma longifolia, which can kill the ring stage of P. falciparum and inhibited the development of young schizont to mature schizont [24]. The contrary result was seen with T. glaucescens which inhibited the parasites at the transition from the trophozoite to the schizont stages [25].…”
Section: Discussionmentioning
confidence: 72%
“…They claimed that was because with subcutaneous route, drugs are directly exposed and absorbed to the bloodstream with the rapid detection of drugs in plasma while with oral administration, the drug is absorbed through the digestive tract and passed through the liver before it is transported via the bloodstream causing inactivation and incomplete absorption. In determining which stage of P. falciparum is susceptible towards E. longifolia treatment, Sholikhah et al (2008) discovered that trophozoites stage of P. falciparum was the weakest when treated with E. longifolia.…”
Section: Anti-malarial Effectmentioning
confidence: 99%